Performance analysis of diesel engine running with tyre-derived fuel - Mohd. Herzwan, Hamzah; Azri, Alias; R., Mamat; Abdul Adam, Abdullah; Sudrajad, Agung; Nur Atiqah, Ramlan; Nur Fauziah, Jaharudin (IOP Publishing, 2019)
In the modern ages, many researches have been conducted to search for alternative fuel. Various source of alternative fuel such as palm, jathropa and rapeseed that are classified as biofuel have been tested to determine its suitability. Besides that, waste product such as waste tyres and plastics also can be processed to yield the alternative fuel. In this paper, performance of a diesel engine operating with tyre-derived fuel (TDF) blended with diesel fuel at several ratios is analysed and compared with diesel fuel. A single cylinder YANMAR TF120M diesel engine is utilized in the experiments where it is operated with constant load exerted to the engine and at variable engine speed ranging from 1200 rpm to 2400 rpm. The performance parameters that was analysed in the paper includes engine power and torque, combustion pressure and exhaust gas temperature. The experimental results show that percentage of TDF blends of 10% in diesel fuel gives significant impact to the engine performance output.